Cutaneous Metastases from Lung Adenocarcinoma - Yu Wang; Ruzeng Xue (Hindawi Limited, 2020)
Cutaneous metastases are unusual presenting symptoms of lung cancer. Therefore, they are prone to be misdiagnosed and missed. The report describes a case of a forty-nine-year-old female with painful zosteriform rashes showing multiple vesicle-like papules localized on the left breast for 10 days. The patient had been diagnosed as lung adenocarcinoma at the department of oncology one year ago. Skin biopsy revealed blue nodular lesions in the dermis, composed of clustered heterogeneous tumor cells with glandular formation. Immunohistochemical stains confirmed the diagnosis of metastatic lung adenocarcinoma.